African biomedical scientists and the promises of "big science". Issue 3 (1st September 2016) - Okeke, Iruka N.
Abstract: An ongoing genomic revolution in biology has exponentially increased the rate, possibilities, scope and cost of biological research. Infectious disease genomics are often justified by the potential they have to ameliorate Africa's disease burden. The molecular biology revolution that preceded genomic science widened the gap between the skill sets of many African biologists and their contemporaries elsewhere. Gap closure through genomics and the application of genomic data to health problems requires participation of, and leadership from, African scientists. However, few African scientists participate in genomics, and providing biological samples is their predominant contribution. Health-related applications are emerging from genomic activity for some infectious diseases that are endemic in Africa but not for many others. This article argues that the arrival of next-generation diagnostics, surveillance tools, drugs and vaccines could be accelerated by improving the nature and degree of participation of African scientists in genomic and post-genomic inquiry.